'Prevotella ihumii' sp. nov. and 'Varibaculum timonense' sp. nov., two new bacterial species isolated from a fresh human stool specimen. (July 2017) - Guilhot, E.; Lagier, J.C.; Raoult, D.; Khelaifia, S.
Abstract: Here we report the main characteristics of 'Prevotella ihumii' sp. nov., CSUR-P3385 T and 'Varibaculum timonense' sp. nov., CSUR-P3369 T isolated in September 2016 from a fresh stool sample of healthy French volunteer woman.